Effect of Molasses and Dried Orange Pulp as Sheep Dietary Supplementation on Physico-Chemical, Microbiological and Fatty Acid Profile of Comisana Ewe's Milk and Cheese - Liotta, Luigi; Randazzo, Cinzia L.; Russo, Nunziatina; Zumbo, Alessandro; Di Rosa, Ambra Rita; Caggia, Cinzia; Chiofalo, Vincenzo (Frontiers in Nutrition, 2019)
The use of agro-industrial by-products for ruminant feed represents an economical and environmental convenient way for reducing waste discharge and waste management costs for food industries. Large amounts of waste from citrus processing industries are available in Sicily, Italy. In the present study the effect of dried citrus pulp as sheep dietary supplementation was evaluated on physico-chemical, microbiological and fatty acid composition of resulting milk and cheese. In detail, pelleted feed integrated with molasses and blond orange pulp replacing cane molasses and beet pulp and part of the maize and sunflower in ration, were administrated to ewes as experimental treatment. The experiment involved sixty Comisana breed sheep’s, divided into two groups and two feeding trials (experimental and control). Ewe’s milk and cheese samples were collected from January to April and analysed for physico-chemical, microbiological and fatty acid profile composition. Results suggested that both experimental milk and cheese were significantly different from controls. In particular, an increase of milk yield and fat content was registered and cheese samples exhibited a significant decrease of pH values and an increase in fat and protein contents. In addition, a higher value of unsaturated fatty acids, polyunsaturated fatty acid and conjugated linoleic acids and a significant improvement of the oxidative stability were observed in experimental cheese samples, indicating the beneficial effect of dietary supplementation. Furthermore, no difference among the main microbial groups was detected, between experimental and control samples, with the exception of streptococci found higher in experimental cheeses and staphylococci, which were significantly reduced by experimental feed. Moreover, the application of culture-independent methods highlighted the dominance of Lactobacillus rhamnosus/casei group in the experimental cheese, suggesting a driving role of the dietary supplementation in the cheese microbiota composition. The present study demonstrated that the inclusion of citrus by-products in the diet of small dairy ruminants had positive effects on milk composition and cheese manufacture.